Effects of zinc supplementation on the immune system and on antibody response to multivalent influenza vaccine in hemodialysis patients - (:unkn) unknown (WICHTIG EDITORE, 1998)
The depression of the immune system in chronic uremia is a well-known phenomenon but the role of serum zinc (Zn) levels on both cell-mediated and humoral immunity is still controversial. The aim of this study was to investigate the effect of Zn supplementation on the immune system and on antibody response to multivalent influenza vaccine (MIV) in hemodialysis patients (HP). Twenty-six HP and I I healthy subjects (HS) were vaccinated with MIV: Hemodialysis patients were randomly divided into two groups. Group 1 (13 HP) was supplemented with 120 mg ZnSO4 after each dialysis session. Group 11 (13 HP) and Grouip III (11 HS) were given placebo. In all cases, the serum Zn levels, CD3, CD4, CD8, CD19, HLA-DR+ cell percentages, CD4/CD8 ratio and CD3+HLA-DR+ cell percentages were determined before and 30 days after vaccination. Antibody levels to subgroups of MIV were also measured. All the baseline parameters studied were not statistically different between Group I and II. However, there was a significant difference between the basal parameters of Group III and the other two groups, except for CD3 and CD4 cell percentages. Serum Zn, CD19 cell percentage and antibody levels to MIV subgroups were significantly increased in Group I at the end of the first month of the study (p<0.01, p<0.05, p<0.001, p<0.001, and p<0.01, respectively), but the other parameters showed no significant changes. The only significant change observed in Groups II and III was an increase in antibody levels to MIV subgroups one month after vaccination. Antibody levels to MIV subgroups, were not statistically different between Groups I and II, but in Group III they were strikingly higher than those of HP (p<0.001). These results led us to conclude that Zn supplementation could not restore the immune parameters and enhance antibody response to MIV in HP.
Keywords: immune system; zinc supplementation; influenza vaccine; antibody response; hemodialysis; CELLULAR-IMMUNITY; THERAPY; SUBSETS